People's Republic of China : Hong Kong Special Administrative Region -- Financial System Stability Assessment. (IMF Staff Country Reports; Country Report ;, 2014)
This Financial System Stability Assessment report on Hong Kong Special Administrative Region (HKSAR) highlights that HKSAR's financial sector is very well regulated, with the capacity to withstand a diversity of shocks. The sector, however, faces major risks, which puts a significant premium on effective liquidity management, macroprudential oversight, and microprudential supervision. The regulation and supervision framework of the financial sector is of a high caliber, and displays a high level of compliance with international standards, but there remains scope for further strengthening. Financial market infrastructures are highly sophisticated, but further enhancements are needed to fully comply with new international standards.